2010
DOI: 10.1111/j.1365-263x.2010.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial and systemic manifestations in 212 paediatric HIV patients from Chennai, South India

Abstract: Oral lesions are a common feature in paediatric HIV infection. Their management is vital to improve the quality of life of the infected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 25 publications
(50 reference statements)
2
27
2
Order By: Relevance
“…Similar association has also been reported by Ranganathan et al (2010) among pediatric HIV patients from South India (22,17). The presence of oral lesions has signifi cant eff ects on the health related quality of life in HIV patients.…”
Section: Discussionsupporting
confidence: 67%
“…Similar association has also been reported by Ranganathan et al (2010) among pediatric HIV patients from South India (22,17). The presence of oral lesions has signifi cant eff ects on the health related quality of life in HIV patients.…”
Section: Discussionsupporting
confidence: 67%
“…In a study with children not under antiretroviral therapy, its prevalence reached 56.1%. 8 Aphthous ulcer and angular cheilitis were also reported in most of the selected studies, being identified in 8 of the 11 papers (Table 2). Aphthous ulcers are common in HIV-infected children and often present with larger sizes.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Its diagnosis is difficult due to the presence of the maternal anti-HIV antibody that crosses the placental barrier and may be detectable in children up to 18 months of age. 6,17 After virus infection, patients can spend several years without manifesting the disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations